1995
DOI: 10.1128/iai.63.2.656-662.1995
|View full text |Cite
|
Sign up to set email alerts
|

Lipopolysaccharides of Actinobacillus pleuropneumoniae bind pig hemoglobin

Abstract: A previous study indicated that lipopolysaccharides (LPS) extracted from Actinobacillus pleuropneumoniae bind two low-molecular-mass proteins, of approximately 10 and 11 kDa, present in porcine respiratory tract secretions (M. Bélanger, D. Dubreuil, and M. Jacques, Infect. Immun. 62:868-873, 1994). In the present study, we determined the N-terminal amino acid sequences of these two proteins, which revealed high homology with the ␣ and ␤ chains of pig hemoglobin. Some isolates of A. pleuropneumoniae were able t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
32
0
3

Year Published

1997
1997
2007
2007

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(36 citation statements)
references
References 39 publications
1
32
0
3
Order By: Relevance
“…As there is essentially no free iron in the human host, most pathogens acquire this indirectly from commonly available iron-containing compounds such as haemoglobin (17). Many are therefore equipped with a mechanism that destroys the heme moiety and extracts the elemental iron from the mammalian host.…”
Section: Discussionmentioning
confidence: 99%
“…As there is essentially no free iron in the human host, most pathogens acquire this indirectly from commonly available iron-containing compounds such as haemoglobin (17). Many are therefore equipped with a mechanism that destroys the heme moiety and extracts the elemental iron from the mammalian host.…”
Section: Discussionmentioning
confidence: 99%
“…We and others demonstrated that A. pleuropneumoniae can utilize pig Hb as a sole source of iron for growth in vitro [5,6]. We recently reported the binding of pig Hb to A. pleuropneumoniae LPS [5,7] and hypothesized that LPS might perform a`docking' function. We also suspect that surface proteins are then involved in the iron uptake from pig Hb.…”
Section: Introductionmentioning
confidence: 99%
“…Several bacterial components, including RTX toxins, lipopolysaccharides (LPS), capsular polysaccharides, outer membrane proteins (OMPs), and proteases appear to contribute to the disease process [4]. We and others demonstrated that A. pleuropneumoniae can utilize pig Hb as a sole source of iron for growth in vitro [5,6]. We recently reported the binding of pig Hb to A. pleuropneumoniae LPS [5,7] and hypothesized that LPS might perform a`docking' function.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Detailed studies of the clinical symptoms of the disease and its characteristic lung lesions, its experimental induction in pigs with viable and sonicated A. pleuropneumoniae, and the endobronchial inoculation of Apx toxins exist [4,5]. The virulence of A. pleuropneumoniae may be considered multifactorial, as is the case with most pathogenic bacteria; the factors involved in pathogenesis include capsular polysaccharides [6], lipopolysaccharides [7], membrane proteins [8,9], adhesion factors [10], exotoxins [5], and urease [11]. Epidemiological data suggest, however, that virulence is strongly correlated with the presence of Apx toxins [4,17].…”
Section: Introductionmentioning
confidence: 99%